The sources of English philosophy in Rosminian thought: the “John Locke” case - Tadini, Samuele (Razón y fe, 2025)
Considering Rosmini’s Logic and Locke’s well-known Essay on the Human Intellect, it is possible to find some elements of comparison, useful to highlight a possible re-reading of the two thinkers, free from pre-established interpretative paradigms. Beyond the differences between the two philosophers, one reader can note a degree of agreement on certain themes, concerning language, the truth of propositions, absolute truth, the demonstration of the existence of God from the concrete I, the probability, the assent, the relationship between reason and faith, and error. This approach is significant and, from a historical-theoretical point of view, negligible by no means.